Theoretical analysis of high electromechanical coupling surface acoustic wave propagating on lead-free Na0.5Bi0.5TiO3–BaTiO3 single crystal. (15th March 2020) - Xie, Qingxiu; Hu, Yuqing; Zhao, Xiangyong; Wang, Feifei; Tang, Yanxue; Zhang, Qiaozhen; Chen, Mingzhu; Shi, Wangzhou; Lin, Di; Luo, Haosu
Abstract : The propagation properties of surface acoustic wave (SAW) on the Na0.5 Bi0.5 TiO3 –BaTiO3 (NBBT) substrate with different crystal cuts were theoretically analyzed by Finite Element Method (FEM). The calculated results, for the NBBT with the optimized electrode type and thickness, indicate the existence of Rayleigh and Sezawa modes with high electromechanical coupling factor K 2 18% and 6.8% respectively, which are considerably higher than that of the conventional lithium niobate (LiNbO3 ) single crystal for SAW applications. The research provides a comprehensive understanding of the SAW propagation characteristics of lead-free NBBT, and explores the promising applications of NBBT in wideband SAW devices. Graphical abstract: Image, graphical abstract